Immature Platelet Fraction Pada Pasien Sepsis: Hubungannya dengan Derajat Keparahan Sepsis - Indrawati, Yeti; Hartono, Benny (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Sepsis and septic shock are major health problems that contribute to increased mortality rates. Early detection and assessment of sepsis severity are critical for appropriate management. This study aims to evaluate the role of Immature Platelet Fraction (IPF) as a biomarker for detecting the development and severity of sepsis in patients, compared to Procalcitonin (PCT). This cross-sectional study involved 42 patients admitted to the Emergency Department of Dr. Saiful Anwar Hospital, Jambi, from May to June 2017. Data collected included clinical parameters, laboratory tests, and the SOFA score. The results showed that IPF levels were significantly higher in patients with severe sepsis compared to those with uncomplicated sepsis (p=0.007) and had a significant positive correlation with the SOFA score (r=0.502, p=0.005). IPF also effectively differentiated septic patients from those with SIRS (p=0.003) and demonstrated diagnostic performance comparable to PCT in distinguishing severe sepsis from uncomplicated sepsis (AUC 0.811 for IPF and 0.868 for PCT). This study concludes that IPF can be a useful biomarker for detecting and assessing the severity of sepsis, with potential widespread application in healthcare settings at a low cost.